Análisis de las políticas comerciales en las importaciones de las subpartidas de partes y piezas de vehículos automóviles Toyota 2,700 c.c y su incidencia en la compañía comautor s.a. - Parrales Zambrano, María Fernanda (2016)
This investigative work is born from the problem detected in the company COMAUTOR S.A., due to different trade policies that the Ecuadorian Government has implemented to restrict imports and regulate the balance of payments, which has led to the increase in the ost of purchase of the products marketed by the company, and therefore reduces the margin of profitability obtained since you must try to keep the sale prices. The selling price is a decisive factor to make the purchases, since on several occasions customers argue that prices have risen compared to previous purchases that have been ade. It should be noted that while the company has implemented strategies of marketing as the advice to customers at the time of sales, with an emphasis on quality that have the original Toyota products; the customers give up and prefer to buy spare parts alternate…..